RUPTURED ABDOMINAL AORTIC ANEURYSM IN THE ERA OF ENDOVASCULAR REPAIR — TOWARDS SINGLE CENTER VALIDATION OF TWO NEW RISK PREDICTION ALGORITHMS - Coelho, Andreia (2017)
Introduction: Despite significant advancements, ruptured abdominal aortic aneurysm (rAAA) remains a life-threatening condition, and the decision whether or not to proceed with surgical intervention is extremely difficult in daily practice. Previous risk prediction models of rAAA mortality developed before EVAR was an option, had their validity questioned in an era where both open repair (OR) and EVAR are available. In 2017, Healey CT et al and von Meijenfeldt GC et al (Dutch Aneurysm Score) published two new mortality prediction models, both based on easily obtained clinical variables and validated in a population submitted to either OR or EVAR. The purpose of this paper was to describe the evolving experience in rAAA management in our centre, and to validate the applicability of the aforementioned scores in our practice. Methods: The clinical data of all patients admitted in our hospital from 2010 to 2016 with the diagnosis of rAAA were retrospectively reviewed and statistical analysis using SPSS V.22 was performed. Results: A total of 71 patients were considered, including 19 EVARs and 52 ORs. There was a significant increase over time in repairs performed by EVAR, and in 2015 the annual rate of EVAR exceeded that of OR. The population of patients submitted to EVAR and OR were comparable in gender, age and co-morbidities with the exception of smoking, more common in the EVAR group (73.7% Vs 36.5%; p=0.005). No cases of intra-operative mortality were registered in the EVAR group, as opposed to 17% in the OR group (p=0,049). 30-day mortality reached 49% in the OR group and 31,6% in the EVAR group (p>0.05). Several pre-operative predictors of outcome were identified: smoking (p=0.005), pre-operative hemodynamic instability (p=0.003) and international normalized ratio (INR) at admission (p<0.0001). As for post-operative preditors of outcome, hemodynamic instability in the ICU was statistically significant (p<0,0001). Binary logistic regression concluded elevated INR and post-operative instability were independent risk predictors of outcome (p<0.05). The mortality score prediction models aforementioned were applied to our population and estimated mortality significantly correlated with real mortality (estimated mortality 41% and 45.3% Vs real mortality 45%; both p<0.0001). Pearson correlation was applied to compare scores and concluded a correlation coefficient of 0.775 (p<0.001), describing a significant positive linear correlation between scores. Conclusions: In recent years, EVAR has increasingly become the procedure of choice for rAAA in our institution. With this evolving approach to rAAA, both score prediction models were retrospectively applied and both accurately predicted mortality in the study population (p<0.001).